Koneksi Matematis Siswa dalam Menyelesaikan Masalah Open-Ended - Nazila Naf’atu Fina; Cholis Sa'dijah; Hery Susanto (Graduate School of Universitas Negeri Malang, 2020)
Abstract: The purpose of this study is to describe the mathematical connection processes of Junior High School students in solving open-ended problems. The type of this research is descriptive qualitative. The data of this research were obtained through tests and interviews. The mathematical connections processes can be seen when students solve open ended mathematics story problems. The connection processes are based on three types of connections, namely concepts connections, procedures connection, and modelling connections. The research concluded that students can use all known information and connect the information so that they get the solution. The process of students’ mathematical connection is happened when the students were able to change the mathematical story problem into mathematical model and to connect mathematical concepts and procedures. However, in general, students only solve one solution even the problem was open ended. The reason is that the students rarely have experience in solving open ended mathematics problem.Abstrak: Tujuan penelitian ini untuk mendiskripsikan proses koneksi matematis siswa SMP dalam menyelesaikan masalah open-ended. Sumber data penelitian ini dari hasil tes masalah open-ended dan hasil wawancara. Koneksi matematis dapat dilihat ketika siswa menyelesaikan soal cerita matematika yang open ended. Proses koneksi matematis siswa dianalisis berdasarkan tiga tipe koneksi, yaitu koneksi konsep, koneksi prosedur dan koneksi pemodelan matematika. Penelitian ini menyimpulkan bahwa siswa dapat menggunakan informasi yang diketahui dan mengoneksikan informasi tersebut sehingga diperoleh penyelesaian. Proses koneksi matematis siswa terjadi ketika siswa mampu mengubah soal ke dalam model matematis dan siswa mampu menghubungkan konsep dan prosedur matematika. Tetapi umumnya siswa hanya menjawab satu penyelesaian walaupun soalnya open ended. Alasannya adalah karena siswa jarang memperoleh pengalaman menyelesaikan soal open-ended.